Analisis Faktor-Faktor Yang Mempengaruhi KonsumenMenggunakan Jasa Ojek Online(Studi Perbandingan Go-Jek Dan Ojek Online Syar'i) - Anggraini, Nur Fitriah, Ahmad Mardalis, SE.,MBA (2017)
This research aim to test influence of factor of product, price, place, promotion, people, evidence physical and of process to decision of consumer in using service of public transport with motorbike (ojek) online. Population and of sample which used in this research is entire consumer of GO-JEK and of Ojek Syar'i counted 100 people. The hypothesis tested in this research use analyzer test of validity, reliabilities test, the classical assumption test, analysis of doubled linear regression, t test, F test, and coefficient of determines (R2). Result of research indicate that product, price, place, promotion, people, evidence physical and of process share positive and significant to decision of consumer at GO-JEK and of ojek syar'i, this matter can be proved with t test. Product, price, place, promotion, people, evidence physical and of processby together have an effect on to decision of consumer at GO-JEK and of ojek syar'i, this provable matter with F test.Result of coefficient of determines (R2)indicating thatproduct, price, place, promotion, people, evidence physical and of processcan explain variability decision of consumerequal to51,8%.